Styrene maleic acid-encapsulated paclitaxel micelles: antitumor activity and toxicity studies following oral administration in a murine orthotopic colon cancer model - Parayath NN; Nehoff H; Norton SE; Highton AJ; Taurin S; Kemp RA; Greish K (International Journal of Nanomedicine, 2016)
Neha N Parayath,1 Hayley Nehoff,1 Samuel E Norton,2 Andrew J Highton,2 Sebastien Taurin,1,3 Roslyn A Kemp,2 Khaled Greish1,4 1Department of Pharmacology and Toxicology, 2Department of Microbiology and Immunology, University of Otago, Dunedin, New Zealand; 3Department of Obstetrics and Gynecology, University of Utah, Salt Lake City, UT, USA; 4Princess Al-Jawhara Centre for Molecular Medicine, Arabian Gulf University, Manama, Kingdom of Bahrain Abstract: Oral administration of paclitaxel (PTX), a broad spectrum anticancer agent, is challenged by its low uptake due to its poor bioavailability, efflux through P-glycoprotein, and gastrointestinal toxicity. We synthesized PTX nanomicelles using poly(styrene-co-maleic acid) (SMA). Oral administration of SMA-PTX micelles doubled the maximum tolerated dose (60 mg/kg vs 30 mg/kg) compared to the commercially available PTX formulation (PTX [Ebewe]). In a murine orthotopic colon cancer model, oral administration of SMA-PTX micelles at doses 30 mg/kg and 60 mg/kg reduced tumor weight by 54% and 69%, respectively, as compared to the control group, while no significant reduction in tumor weight was observed with 30 mg/kg of PTX (Ebewe). In addition, toxicity of PTX was largely reduced by its encapsulation into SMA. Furthermore, examination of the tumors demonstrated a decrease in the number of blood vessels. Thus, oral delivery of SMA-PTX micelles may provide a safe and effective strategy for the treatment of colon cancer. Keywords: oral delivery, anticancer nanomedicine, CT-26, enhanced permeability and retention (EPR) effect, HUVEC, antiangiogenic